Are socio-economic inequalities in diet and physical activity a matter of social distinction? A cross-sectional study - Oude Groeniger, Joost (Int J Public Health, 2019)
OBJECTIVES: To explore whether ‘distinction’, a well-known mechanism that produces and reproduces social inequalities, can explain the socio-economic gradient in healthy diet and physical activity in contemporary obesogenic environments. If this is the case, we would expect a well-established indicator of distinction, ‘highbrow’ cultural participation, to be associated with a healthy diet and physical activity, while adjusting for education and income. METHODS: Data from participants (25–75 years) of the 2014 wave of the Dutch GLOBE study (N = 2812) were used to analyse the association between ‘highbrow’ cultural participation (e.g. annual frequency of visits to museums, ballet, concerts, theatre) and sports participation, leisure-time walking and cycling, and fruit and vegetable intake, adjusted for education, income and other confounders. RESULTS: Both highbrow cultural participation and healthy behaviours were more prevalent among high educational groups. Cultural participation was strongly associated with all health behaviours, even when adjusted for education and income. CONCLUSIONS: Our findings suggest that health behaviours, similar to highbrow cultural participation, are adopted as an expression of social distinction. This distinction mechanism may be an important determinant of health behaviour inequalities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00038-019-01268-3) contains supplementary material, which is available to authorized users.